1999
DOI: 10.1016/s0886-3350(99)00011-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional vision and corneal changes after laser in situ keratomileusis determined by contrast sensitivity, glare testing, and corneal topography

Abstract: Functional vision changes do occur after LASIK. The optical quality of the cornea is reduced and the asphericity becomes oblate. Changes in functional vision worsen as the target contrast diminishes and the pupil size increases. These findings indicate that the oblate shape of the cornea following LASIK is the predominant factor in the functional vision decrease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
141
0
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(149 citation statements)
references
References 13 publications
4
141
0
4
Order By: Relevance
“…However, the range of safe dioptric correction for these procedures has been progressively narrowed as a consequence of the mid and long-term complications observed, particularly in cases of high refractive error, such as keratectasia, 1 corneal haze, 2 regression, 3 dry eye, 4 or poor postoperative visual quality. 5,6 It has been shown that photoablative refractive surgery in high ametropia can lead to a significant increase in ocular aberrations 5 and decrease in visual performance. 6 Furthermore, corneal photoablation has a decreased predictability for the correction of high refractive error because of the unknown and unpredictable effects on corneal biomechanics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the range of safe dioptric correction for these procedures has been progressively narrowed as a consequence of the mid and long-term complications observed, particularly in cases of high refractive error, such as keratectasia, 1 corneal haze, 2 regression, 3 dry eye, 4 or poor postoperative visual quality. 5,6 It has been shown that photoablative refractive surgery in high ametropia can lead to a significant increase in ocular aberrations 5 and decrease in visual performance. 6 Furthermore, corneal photoablation has a decreased predictability for the correction of high refractive error because of the unknown and unpredictable effects on corneal biomechanics.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 It has been shown that photoablative refractive surgery in high ametropia can lead to a significant increase in ocular aberrations 5 and decrease in visual performance. 6 Furthermore, corneal photoablation has a decreased predictability for the correction of high refractive error because of the unknown and unpredictable effects on corneal biomechanics. 7 Intraocular refractive procedures have become a safe, efficient and predictable alternative for treating high ametropias when the use of corneal photoablative procedures is not possible or high risk.…”
Section: Introductionmentioning
confidence: 99%
“…For the first three to six months, the patient intermittently experienced symptoms of dry eyes (Low 2012), fluctuation and; clarity of vision. However, these did not affect her functional daily task and the slight glare and haloes, which were a part of the healing process in corneal refractive surgery (Holladay 1999). The usage of artificial tears gave a smoother ocular surface, thus making the patient feeling more comfortable and having a clearer vision.…”
Section: Discussionmentioning
confidence: 96%
“…Holladay et al (15) published a study showing that large pupil patients suffered from visual disturbance and degradation, the optic of the cornea leading to decrease in contrast sensitivity after LASIK. Halos and false images after PRK occur more often at night in young myopic patients with greater pupillary diameters.…”
Section: Discussionmentioning
confidence: 99%